The Implementation of Total Physical Response (TPR) in Teaching Speaking - Ahmad Jazuli; Faishol Hadi; Achmad Anang Darmawan (STKIP AL HIKMAH SURABAYA, 2024)
Generally, speaking skill is one of the essential skills that must be acquired by students at school. The students are hoped to be able to communicate in English in their daily activities. Event though, student unrarely use it because feeling unconfident and absolutely need a way to solve the problem. This research would investigate the implementation of TPR in Teaching Speaking. To analyze how TPR is used by teacher and students’ response in learning English especially speaking skill, qualitatitive methodologies ar employed. Teacher and English learners from SMPN 1 Purwosari in the 8th grade served as the participants. Observation, questionnaires, and interviews were used to collect the data. The most students gave positive response toward the implemetation of TPR in learning speaking. It was proved from the result of the interview and questionnare. The students had fun to learn English in speaking by using many movements during learning activity and they were able to follow their teacher’s intruction well. However, few students did not interest toward TPR in learning English speaking lesoon. The suggestion for other researchers is to investigate the implementation TPR in teaching other languages aspect such as grammar. The researchers are also suggested to investigate the effectiveness of TPR teaching method to improve students’ particular English skill.